1989
DOI: 10.1080/00219266.1989.9655047
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural modifications and increased predation risk of Gammarus pulex infected with Polymorphus minutus

Abstract: 1989) Behavioural modifications and increased predation risk of Gammarus pulex infected with Polymorphus minutus , Journal of Biological Education, 23:2, 135-141 To link to this article: http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Cezilly & Perrot‐Minnot (2005) review a number of examples of trophically transmitted parasites where manipulation increases predation by both host and non‐host species. For example, although the definitive hosts of the acanthocephalan Polymorphus minutus are aquatic birds, P. minutus increased the susceptibility of G. pulex to fish predators (Marriott et al. 1989).…”
Section: Parasites and Predatorsmentioning
confidence: 99%
“…Cezilly & Perrot‐Minnot (2005) review a number of examples of trophically transmitted parasites where manipulation increases predation by both host and non‐host species. For example, although the definitive hosts of the acanthocephalan Polymorphus minutus are aquatic birds, P. minutus increased the susceptibility of G. pulex to fish predators (Marriott et al. 1989).…”
Section: Parasites and Predatorsmentioning
confidence: 99%
“…P. minutus is a trophically transmitted parasite which exploits amphipods as intermediate hosts and waterbirds as definitive hosts (Kennedy, 2006). Infection with P. minutus is known to influence G. roeseli's distribution , reproduction (Dezfuli et al 2008), physiology (Piscart et al 2007;Sures and Radszuweit, 2007), and behaviour (Marriott et al 1989;Bauer et al 2005;Médoc et al 2006Médoc and Beisel, 2008), but nothing has been reported regarding its trophic ecology once infected.…”
Section: Introductionmentioning
confidence: 99%
“…The question of specificity was raised since it has been stressed that non‐host predators sometimes benefit from feeding on the profitable prey that are manipulated intermediate hosts (Table 1: Marriott et al 1989, Ness and Foster 1999, Mouritsen and Poulin 2003, Kaldonski et al 2008, Seppälä et al 2008). It has been proposed that the lowest degree of specificity required for a host manipulation strategy to be adaptive may be tightly connected to the predation risk hosts are exposed to without manipulation (initial predation risk, Seppälä and Jokela 2008), or may depend on whether parasites show age‐dependent mortality or die only through random predation of their host (Parker et al 2009).…”
Section: From Multidimensionality To Specificitymentioning
confidence: 99%